2008
DOI: 10.1158/1055-9965.epi-08-0461
|View full text |Cite
|
Sign up to set email alerts
|

Age-Incidence Curves of Nasopharyngeal Carcinoma Worldwide: Bimodality in Low-Risk Populations and Aetiologic Implications

Abstract: The distinct geographic variation in the global incidence of nasopharyngeal carcinoma reflects a complex etiology involving viral, environmental, and genetic components. The high to intermediate rates observed in endemic areas contrast markedly with the uniformly low rates seen in much of the world. An interesting epidemiologic observation is the early peak in ageincidence curves observed in certain geographically disparate populations, suggestive of distinct causal entities and the possible exhaustion of susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
98
2
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(109 citation statements)
references
References 34 publications
5
98
2
4
Order By: Relevance
“…Nasopharyngeal carcinoma (NPC) is a rare neoplasm in most countries (<1 × 10 −5 person-years), but a much higher incidence has been observed in southern China (20 − 50 × 10 −5 person-years) (1)(2)(3) . Infection with the Epstein-Barr virus (EBV) is considered a key cause of NPC (1) , but the ubiquity of EBV suggests that other cofactors, such as diet, may have a role in NPC aetiology and may contribute to the remarkable geographic variation (4,5) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nasopharyngeal carcinoma (NPC) is a rare neoplasm in most countries (<1 × 10 −5 person-years), but a much higher incidence has been observed in southern China (20 − 50 × 10 −5 person-years) (1)(2)(3) . Infection with the Epstein-Barr virus (EBV) is considered a key cause of NPC (1) , but the ubiquity of EBV suggests that other cofactors, such as diet, may have a role in NPC aetiology and may contribute to the remarkable geographic variation (4,5) .…”
mentioning
confidence: 99%
“…Although many other studies have found an inverse association between dietary (17)(18)(19)(20)(21)(22)(23) or blood (24)(25)(26)(27) folate and the risk for head and neck cancer, the numbers of NPC cases in these studies were generally <100. In addition, all of these studies were conducted among populations with dietary habits and NPC risks different from those of the Chinese in south China (1)(2)(3) . Thus, further study of the folate-NPC association in high-risk Chinese adults is necessary.…”
mentioning
confidence: 99%
“…Several randomized trials including that of the Alsaraf Intergroup in 1999 and the metaanalysis of Baujat and al. confirmed that the overall survival benefit was limited to the concomitant chemoradiotherapy group (9,10,11) . Lin and al found a benefit of concomitant radiochemotherapy in overall survival of 90%, recurrence-free survival of 92% and local control of 95% at three years (12) .…”
Section: Figure 2: Survival Curvesmentioning
confidence: 64%
“…Nasopharyngeal carcinoma (NPC) arises from the epithelial lining of the nasopharynx but frequently develops at the fossa of Rosenmuller around the ostium of the Eustachian [17], this is similar to low incidence areas [12]. The maximum incidence in 4th and 5th decade is also seen in the study of Boljesíková et al [13] India has low over all incidence of NPC which is comparable to UK with annual incidence of 0.9 per million population [1,12].…”
Section: Discussionmentioning
confidence: 99%